Ten new species of parasitoid wasps Mnioes Townes, 1946 (Hymenoptera: Ichneumonidae: Banchinae) described from Peru - Alvarado, Mabel (Zootaxa, 2020)
Mnioes Townes is a predominantly Neotropical genus of the family Ichneumonidae, mainly documented from Central America and, until now, with no described species from South America. In this paper, ten new species are described from Peru: Mnioes attenboroughi sp. nov., M. huk sp. nov., M. iskay sp. nov., M. kinsa sp. nov., M. pisqa sp. nov., M. poncei sp. nov., M. pusaq sp. nov., M. qanchis sp. nov., M. soqta sp. nov., and M. tawa sp. nov. A key to the Peruvian species and maps of their geographical distribution are also presented.